2014
DOI: 10.1186/1743-0003-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetic neuropathy severity classified by a fuzzy model in muscle dynamics during gait

Abstract: BackgroundElectromyography (EMG) alterations during gait, supposedly caused by diabetic sensorimotor polyneuropathy, are subtle and still inconsistent, due to difficulties in defining homogeneous experimental groups with a clear definition of disease stages. Since evaluating these patients involve many uncertainties, the use of a fuzzy model could enable a better discrimination among different stages of diabetic polyneuropathy and lead to a clarification of when changes in muscle activation start occurring. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 37 publications
2
85
3
Order By: Relevance
“…] aim at taking into account uncertainties often by applying fuzzy logic where truth values of variables vary [Watari et al. ; Mak, ; Miranda and Felipe, ]. Fuzzy sets and logic are largely dependent on the initial setup.…”
Section: Applications Of the Pmmentioning
confidence: 99%
“…] aim at taking into account uncertainties often by applying fuzzy logic where truth values of variables vary [Watari et al. ; Mak, ; Miranda and Felipe, ]. Fuzzy sets and logic are largely dependent on the initial setup.…”
Section: Applications Of the Pmmentioning
confidence: 99%
“…Altered activity at the knee muscles, especially the extensors, have also been found on DPN individuals. Studies have described a delayed peak activity and a lower activity of the vastus lateralis muscle at heel strike during gait (Abboud, Rowley and Newton, 2000;Akashi et al, 2008;Sacco, Akashi and Hennig, 2010;Watari et al, 2014) and an earlier onset at initial contact with a diminished activity was reported during pre-swing phase for rectus femoris (Sawacha, Spolaor, et al, 2012). Altered activity of vastus lateralis has also been described during stair descent/ascent , suggesting that the presence of DPN alters the muscle coordination in different locomotor tasks.…”
Section: Muscle Activation Pattern Of Diabetic Neuropathic Individualmentioning
confidence: 98%
“…The motor dysfunction caused by DPN interferes with muscular activity of the lower limbs while performing daily living tasks (Abboud, Rowley and Newton, 2000;Akashi et al, 2008;Sacco, Akashi and Hennig, 2010;Watari et al, 2014). The existing literature has shown altered activity at the ankle muscles in the presence of DPN during gait stance phase, reporting a delayed (Akashi et al, 2008;Sacco, Akashi and Hennig, 2010) and lower activation of gastrocnemious muscles, and a delayed activation of tibialis anterior muscle (Abboud, Rowley and Newton, 2000;.…”
Section: Muscle Activation Pattern Of Diabetic Neuropathic Individualmentioning
confidence: 99%
See 2 more Smart Citations